2011
DOI: 10.1111/j.1365-2842.2011.02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of 2D and 3D imaging in odontogenic maxillary sinusitis: a review of literature

Abstract: Belgium SUMMARY This review aims to explore whether 3D imaging offers an added value in diagnosis of odontogenic sinusitis. Odontogenic maxillary sinusitis accounts for approximately 10-12% of maxillary sinusitis cases. Proper diagnosis of odontogenic sinusitis is based on a thorough dental and medical examination and crucial to ensure therapeutic efficacy. To establish the odontogenic cause of maxillary sinusitis, 2D and 3D imaging modalities may be considered, each presenting distinct advantages and drawback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
15

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 36 publications
(41 reference statements)
0
52
0
15
Order By: Relevance
“…They found that endoscopy was not a proper diagnostic method for the diagnosis of concha and septum anomalies [32]. Shahbazian and Jacobs [33] reviewed the accuracy of 2D and 3D imaging in the diagnosis of odontogenic maxillary sinusitis and found that CBCT was superior to 2D imaging in the diagnosis of maxillary sinusitis because conventional CT may obscure the odotogenic origin of maxillary sinusitis. In Korea, Woo et al [10] evaluated the efficacy of CBCT for the preoperative evaluation of endoscopic sinus surgery in 50 patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found that endoscopy was not a proper diagnostic method for the diagnosis of concha and septum anomalies [32]. Shahbazian and Jacobs [33] reviewed the accuracy of 2D and 3D imaging in the diagnosis of odontogenic maxillary sinusitis and found that CBCT was superior to 2D imaging in the diagnosis of maxillary sinusitis because conventional CT may obscure the odotogenic origin of maxillary sinusitis. In Korea, Woo et al [10] evaluated the efficacy of CBCT for the preoperative evaluation of endoscopic sinus surgery in 50 patients.…”
Section: Discussionmentioning
confidence: 99%
“…L'épaississement muqueux et l'accumulation des sécrétions associées à la sinusite réduisent l'air contenu au niveau du sinus maxillaire et le font devenir de plus en plus radio-opaque [7][8][9]. La tomodensitométrie s'impose en cas d'atteinte polysinusienne (en particulier ethmoïdale), les aspects les plus fréquemment rencontrés sont des opacités localisées ou diffuses, en cadre ou limitées au bas fond sinusien ; parfois il s'agit d'un niveau hydroaérique ou d'une micro-opacité au sein d'une opacité complète.…”
Section: Discussionunclassified
“…La tomodensitométrie s'impose en cas d'atteinte polysinusienne (en particulier ethmoïdale), les aspects les plus fréquemment rencontrés sont des opacités localisées ou diffuses, en cadre ou limitées au bas fond sinusien ; parfois il s'agit d'un niveau hydroaérique ou d'une micro-opacité au sein d'une opacité complète. Les relations dentosinusiennes et l'état des apex dentaires sont bien étudiés en cherchant une éventuelle dent antrale infectée [7,9,10].…”
Section: Discussionunclassified
“…Eine Kontrastmittelgabe wird bisher nicht praktiziert. Bei Fragestellungen im Hochkontrastbereich (Luft, Sekret, Schleimhaut, Knochen), zur Klä-rung der Anatomie oder zur Fremdkör-perdetektion ist die DVT dagegen sehr gut geeignet [25]. Als weiterer Vorteil ist die häufig unmittelbare Verfügbarkeit der Untersuchung zu nennen (.…”
Section: Bei Der Dvt Steht Der Gutenunclassified